Young family expenditure in Malaysia: Main expenditure composition for dependent - Debbie Dyana Jun Jinideh; Janice L. H. Nga; Wijaya Kamal Ramlan; Jonghyun Park (GRRI, 2018)
The cost of living is a significant issue in Malaysia. It has been discussed not only by the researcher, but also been discussed among youth themselves. As the economy becoming more challenging, the cost of living is rising as the price of goods and services increases. The expenditure pattern and its cost differ among youth due to the differences in their needs as well as their preferences. This paper focuses on the expenditure of young families with dependents in Malaysia. The dependent in this paper refer to the children that the young families need to support. In that, the expenditure incurred by the young families refers to the items spent for the necessity in raising their children. This paper discusses on the ratio or expenditure pattern distributed among items that spent on their children within their monthly expenditure. The analysis is based on the selected respondents that meet the criteria of this study i.e. married youth with dependent. The respondents for this paper were shortlisted from the total of 1132 respondents in which 600 respondents were collected via online survey and the rest 532 feedback acquired by hardcopy questionnaire. The data were analysed using the SPSS. A multiple regression equation is attempted to explain the relationship between the expenditure for items spent on the children necessity and the total monthly married youth expenditure for a month. This paper is an attempt in generating an equation for the young family expenditure pattern based on the composition spent for the necessity of their children in Malaysia. While this paper may be a new attempt to formulate an equation, it is helpful to offer important traits of composition expenditure as well as in identifying what is necessity of priority and major expenses of the young family in raising their children.